Macromol. Mater. Eng. 10/2013. Issue 10 (4th October 2013) - Krishnan, Ranganathan; Sundarrajan, Subramanian; Ramakrishna, Seeram
<x xml:space="preserve">Abstract</x> Cover: The fabrication of polyelectrolyte nanofibrous scaffolds from aqueous polymer solutions through a simple and versatile green electrospinning process is presented. The generation of different architectures under various spinning conditions and the application of polyelectrolyte scaffolds from polysaccharides and biopolymers for skin, cartilage, heart, and bone applications are reviewed. Further details can be found in the article by R. Krishnan, S. Sundarrajan, * and S. Ramakrishna* on page 1034. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>